QUALITY MANAGEMENT SYSTEMS FOR DESIGN CONSULTANTS - A CASE STUDY IN COMMERCIAL PROJECT CONSULTANTS IN THE GREATER JAKARTA AREA - Jason Lim; Joshua Tjandra (Jurnal Ilmiah Ekonomi Bisnis, 2023)
Standardization of Quality Management System (QMS) for design consultants has not been established as a regulation by Indonesian local government. As a result, quality of design consultants varies. The research combined literature review and interviews with experts in design consultants, addressing 12 elements of quality management system based on ISO 9001 AND 9004. The quality data gathered from consultants were then verified with major users to find gaps and point of improvements. There were four finding of mismatch, namely: documentation and follow up by consultant to feed-back and complaints of service user, product verification before it reaches the service user, innovation to process, and design result. These four findings of mismatch were then looked into further with the corresponding consultant and service user. As the end of the study, a model completed with activities briefs and checklists were proposed to address mismatch and as improvement.